The psychological analysis of bully profile via peers report (The Journal of Psychology and Sociology, 2021)
This article is devoted to the problem of bullying, the various forms, and manifestations of which can be distinguished in all spheres of life of modern youth. The presented article examines the prevalence of bullying in higher educational institutions in Aktobe. The aim of the study was to identify the attitude of respondents in two groups: Kazakh-speaking and Russian-speaking to the image of the bully and to establish differences in approaches to assessing aggressive behavior. Our respondents were senior un- dergraduate students in different areas of study of private and public universities in Aktobe (N = 115), 58 were Russian-speaking students, 57 were Kazakh-speaking students, age (Me = 18.7). For the study, a questionnaire was developed, through which the personality traits possessed by bully were identified. The questionnaire used a bipolar scale for describing the personality of the bully, consisting of ten paired antonyms. The subjects noted several bully features, such as “dominance”, “psychological stability”. As a result of the experiment, it was revealed that there are certain features in assessing the bully profile associated with the language of the respondents. 47.5% of the participants in the Russian-speaking group noted that they were “outside observers”, 27% – victims. In the Kazakh-speaking group, 37.1%  of participants were bullied at school, 40.4% witnessed bullying. At the same time, as a result of the study, there were mixed answers of respondents in the Kazakh-speaking sample, who at the same time endowed the bully with contradictory characteristics that have the features of a rapist and a victim. The differences in approaches and assessment of the bully image in the two samples are significant, which requires further research.Key words: bullying, semantic differential, bully, students, dominance, victims, stigmatization.